FeNi-C catalytic modified magnesium hydride hydrogen storage material and preparation method thereof
By ball milling the FeNi@C catalyst with magnesium hydride, the MgH2-FeNi@C composite material was formed, which solved the problem of poor hydrogen liberation performance of magnesium hydride and achieved efficient hydrolysis and hydrogen production performance.
Patent Information
- Application Number
- CN202411488081.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-25
AI Technical Summary
The poor hydrolibration hydrogen performance of magnesium hydride limits its application in hydrogen storage materials.
By preparing the FeNi@C catalyst and ball milling with magnesium hydride, the MgH2-FeNi@C composite material is formed, and its hydrolysis hydrogen production performance is improved.
The hydrolysis hydrogen production performance of magnesium hydride is significantly improved, the activation energy of the hydrolysis reaction is reduced, and the hydrogen production volume and hydrogen production rate are improved.
Smart Images

Figure CN119503727A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials, and in particular relates to a FeNi@C catalytically modified magnesium hydride hydrogen storage material and a preparation method thereof. Background Art
[0002] Hydrogen energy is a clean secondary energy carrier that can achieve sustainable energy utilization, with advantages such as high energy density per unit mass and wide sources. To achieve the widespread application of hydrogen energy, there are still three major problems: production, storage and application. Among them, the storage of hydrogen energy is the key to limiting its widespread use.
[0003] The main methods of hydrogen storage are high-pressure gas hydrogen storage, low-temperature liquid hydrogen storage, organic liquid hydrogen storage and solid-state hydrogen storage. So far, the technology of high-pressure gas hydrogen storage is relatively mature, but the stored hydrogen pressure is too high and the safety is poor; low-temperature liquid hydrogen storage has the advantage of high volume density, but liquid hydrogen is very easy to evaporate, resulting in excessive energy consumption and high costs; organic liquids have good solubility, but organic liquids used for hydrogen storage usually contain impurities to varying degrees; solid-state hydrogen storage has the advantages of low cost, high volume density and good safety, but choosing suitable solid hydrogen storage materials to increase hydrogen storage capacity and performance is a key issue that needs to be solved urgently.
[0004] As a new type of solid hydrogen storage material hydrogen supply technology, metal hydride hydrolysis has received great attention in recent years. As a solid hydrogen storage material, magnesium hydride has the advantages of low price and high theoretical hydrogen storage capacity, and has always been a popular material for research. However, the stable thermodynamic properties of magnesium hydride hydrolysis, the formation of magnesium hydroxide passivation layer and the slow hydrogen adsorption and desorption kinetics limit its application range. Summary of the invention
[0005] One object of the present invention is to provide a method for preparing a FeNi@C catalytically modified magnesium hydride hydrogen storage material, which effectively solves the problem of poor hydrolysis hydrogenation performance of magnesium hydride.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a FeNi@C catalytically modified magnesium hydride hydrogen storage material, comprising the following steps.
[0007] S1. Preparation of catalyst precursor: Glucose, ferric nitrate nonahydrate and nickel nitrate hexahydrate were dissolved in deionized water, and then urea was added and stirred at room temperature for 1 hour until all the reagents were dissolved. The obtained solution was transferred to a hydrothermal reactor for heating and insulation reaction, and then the solution was taken out and centrifuged and washed 3 times. The obtained product was placed in an oven for drying to obtain the catalyst precursor FeNi-LDH for later use.
[0008] S2. Preparation of catalyst: placing the catalyst precursor FeNi-LDH in a tubular furnace and heating it for pyrolysis to obtain the catalyst FeNi@C for later use.
[0009] S3. Preparation of FeNi@C catalytically modified magnesium hydride hydrogen storage material: MgH 2 The ball milling was performed with FeNi@C. After each 10-min operation, the ball milling was stopped for 5 min and then reversed. The total ball milling operation time was 5 h. At the end of the ball milling, MgH 2 -FeNi@C composite materials.
[0010] Furthermore, in step S1, the ratio of glucose, ferric nitrate nonahydrate, nickel nitrate hexahydrate, deionized water and urea is 3 mmol:1.5 mmol:3 mmol:50 mL:8 mmol.
[0011] Furthermore, in step S1, the conditions for heating and heat preservation in the hydrothermal reactor are: heat preservation at 180°C for 12 hours; and the conditions for oven drying are: drying at 40°C for 12 hours.
[0012] Furthermore, in step S2, the conditions for the temperature-raising pyrolysis are: raising the temperature to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and then maintaining the temperature for 2 hours.
[0013] Further, in step S3, MgH 2 The mass ratio of FeNi@C to FeNi@C is 90~99:10~1; the mass ratio of balls to materials during ball milling is 40:1, and the ball milling speed is 300r / min.
[0014] Further, in step S3, MgH 2 The mass ratio of FeNi@C is 95:5.
[0015] Another object of the present invention is to provide a FeNi@C catalytically modified magnesium hydride hydrogen storage material, which is prepared by the preparation method described in the above embodiment.
[0016] Another object of the present invention is to provide a method for producing hydrogen by hydrolysis, wherein the FeNi@C catalytically modified magnesium hydride hydrogen storage material prepared in the above embodiment is added to a magnesium chloride solution, and the hydrolysis reaction is completed in a constant temperature water bath and magnetic stirring. The timing starts when the magnesium chloride solution is added, and the generated hydrogen is collected by a water drainage method.
[0017] Furthermore, the concentration of the magnesium chloride solution is 0.1 mol / L, and the usage ratio of the magnesium chloride solution to the FeNi@C catalytically modified magnesium hydride hydrogen storage material is 10 mmol:1 g.
[0018] Furthermore, the temperature of the water bath is 30°C, 40°C, 50°C or 60°C, the speed of the magnetic stirring is 200 r / min, and the hydrolysis reaction time is 1 h.
[0019] Compared with the prior art, the beneficial technical effects of the present invention are: the preparation method of the present invention is simple, the hydrogen production efficiency is high, and the pollution is small. The FeNi@C catalytic modified magnesium hydride hydrogen storage material prepared by the present invention is doped with a bimetallic catalyst FeNi@C, which greatly improves the performance of magnesium hydride hydrolysis hydrogen production and effectively reduces the activation energy of the hydrolysis reaction of magnesium hydride. The present invention is expected to be applied to portable power supply devices or hydrogen supply sources for fuel cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The catalyst FeNi@C prepared in Example 1 and the ball-milled MgH 2 -XRD pattern of FeNi@C composite material.
[0021] Figure 2 is a scanning electron microscope image of the catalyst FeNi@C prepared in Example 1.
[0022] Figure 3 is the MgH prepared in Example 1 2 -Scanning electron microscope image of FeNi@C composite.
[0023] Figure 4 It is a schematic diagram of the structure of the hydrolysis reaction generator in Example 1.
[0024] Figure 5 MgH prepared in Example 1 and Comparative Example 1 2 -Hydrolysis reaction kinetics curve of FeNi@C composite material at 30℃.
[0025] Figure 6 MgH prepared in Example 1 and Comparative Example 2 2 -Hydrolysis reaction kinetics curve of FeNi@C composite material at 30℃.
[0026] Figure 7 is the MgH prepared in Example 1 2 -Hydrolysis reaction kinetics curves of FeNi@C composite materials at different temperatures.
[0027] Figure 8 Yes Figure 7 Results The Arrhenius curve was fitted by JMA equation.
[0028] Explanation of the reference numerals: three-necked flask-1; test tube rack-2; constant temperature magnetic stirring water bath-3; Monteggia washing bottle-4; weighing beaker-5; electronic balance-6. DETAILED DESCRIPTION
[0029] Example 1: Magnesium hydride (MgH 2 ) powder was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd. (Shanghai, China). Nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O), ferric nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), urea (CH 4 N 2 O) and glucose (C 6 H 12 O 6 ) and other analytical grade chemicals were purchased from Aladdin Co., Ltd. (Shanghai, China).
[0030] The preparation method of FeNi@C catalytically modified magnesium hydride hydrogen storage material is as follows.
[0031] First, prepare the catalyst precursor FeNi-LDH: dissolve 0.54048g glucose, 0.6060g ferric nitrate nonahydrate and 0.8123g nickel nitrate hexahydrate in 50mL deionized water, then add 0.4805g urea and stir at room temperature for 1h. After all the reagents are dissolved, transfer the resulting solution to a hydrothermal reactor, and then heat the hydrothermal reactor to 180°C and keep it for 12h. Then take out the solution and wash it by centrifugation 3 times. The obtained product is placed in a 40°C oven and dried for 12h to obtain the catalyst precursor FeNi-LDH for later use.
[0032] Secondly, the catalyst FeNi@C was prepared by high-temperature pyrolysis. The catalyst precursor FeNi-LDH was heated to 700°C at a heating rate of 5°C / min in a tubular furnace under a nitrogen environment, and then pyrolyzed for 2 hours to prepare the catalyst FeNi@C.
[0033] In order to determine the phase structure of the catalyst FeNi@C, the catalyst was tested by X-ray diffraction. Figure 1 As shown, the crystal phase of the catalyst FeNi@C is determined to be FeNi 3 .
[0034] Finally, MgH was prepared by high-energy ball milling. 2 -FeNi@C composite material (i.e., FeNi@C catalytically modified magnesium hydride hydrogen storage material). MgH 2 Ball milling with FeNi@C, MgH 2The mass ratio of FeNi@C to FeNi@C is 95:5, the mass ratio of ball to material is 40:1, and the rotation speed is 300r / min; after each ball milling for 10min, stop for 5min, and then reverse the ball milling; the total ball milling operation time is 5h (referring to the ball mill operation time, excluding the intermediate stop time); after the ball milling is completed, MgH 2 -FeNi@C composites. The samples were handled and stored in a glove box filled with argon during the preparation process (i.e., MgH 2 and FeNi@C were weighed and canned in the glove box, and the ball-milled MgH 2 -FeNi@C composites were collected, weighed and stored in a glove box), where H 2 O and O 2 The concentration is less than 0.1ppm to prevent the composite material from reacting with water and air.
[0035] To verify that MgH 2 -FeNi@C composite material to see if it reacts. 2 -FeNi@C composite material was subjected to X-ray diffraction test, and the results are as follows Figure 1 As shown, the ball milling process is only a physical process and no other phases are produced.
[0036] Figure 2 This is a scanning electron microscope picture of the catalyst. From the picture, we can see that the synthesized precursor FeNi-LDH with a stable and unique flower-like structure remains basically unchanged after calcination to obtain flower-like FeNi@C. This structure has better surface dispersibility and more catalytic active sites. The nano-alloy particles on the carbon structure skeleton can be better dispersed in the subsequent ball milling process.
[0037] To observe MgH 2 -FeNi@C composites, MgH 2 -FeNi@C composites were tested by scanning electron microscope. Figure 3 As shown. MgH after ball milling 2 -FeNi@C composite material has uniform particle size dispersion without large particle agglomeration, which indicates that the catalyst FeNi@C plays a good grinding aid role in the ball milling process. At the same time, the uniform dispersion of the composite material can also better react with the hydrolyzate (MgCl 2 The nano-FeNi alloy in the catalyst adheres to the MgH 2 The surface of the substrate destroys the MgH 2 The structural stability of the transition metal plays a catalytic role.
[0038] Hydrogen production by hydrolysis through volumetric displacement method: The hydrolysis reaction generator independently built by the applicant is as follows: Figure 4 As shown, the hydrolysis reaction is carried out in a three-necked flask 1, and then the three-necked flask 1 is fixed in a constant temperature magnetic stirring water bath 3 through a test tube rack 2, the plug holes on the left and right sides are sealed, and the upper opening is connected to the short tube in the middle of the Monteggia washing bottle 4 through a rubber plug and a rubber hose for air intake, and then the collected gas presses the water into the weighing beaker 5 connected to the long tube of the washing bottle through air pressure, and then the weighing beaker 5 is placed on an electronic balance 6 to record the mass of the discharged water at all times. Specific operation method: First check the air tightness of the entire device, and then weigh 0.1g MgH 2 -FeNi@C composite material, and then hydrolyzed in 10mL 0.1mol / L magnesium chloride aqueous solution at constant temperature for 1h, and stirred continuously. In this embodiment, magnetic stirring was performed at a speed of 200r / min. During the entire reaction process, hydrogen enters the Monte Carlo washing bottle 4 through the pipeline, and the discharged water is introduced into the weighing beaker 5 placed on the electronic balance 6, and the mass reading is taken once a minute. Since the density of water is 1g / cm 3 , the mass of water expelled is equivalent to the volume of hydrogen produced, which helps determine the hydrogen production of the composite.
[0039] Comparative Example 1: The difference from Example 1 is that the mass ratios of magnesium hydride and FeNi@C catalyst are different. The mass ratios of magnesium hydride and FeNi@C catalyst in each comparative example are 99:1, 98:2, 97:3, 96:4, 94:6, 93:7, 92:8, and 90:10, respectively.
[0040] The results are as follows Figure 5 As shown, the magnesium hydride and FeNi@C catalysts have a maximum yield of 93.76% when the mass ratio is 95:5. Therefore, after comprehensive analysis and comparison, the addition amount of the optimal catalyst is 5wt%.
[0041] Comparative Example 2: The difference from Example 1 is that the total running time of the ball mill is different. The total running time of the ball mill in each comparative example is 1 h, 3 h and 7 h respectively.
[0042] The results are as follows Figure 6 As shown, Example 1 with a total ball milling operation time of 5 h has the fastest rate within 30 min of hydrolysis and has the largest hydrogen release amount of 1584.8 mL / g after 1 h of hydrolysis. Therefore, when the mass ratio of magnesium hydride to FeNi@C catalyst is 95:5, the total ball milling operation time of 5 h is the optimal ball milling process time.
[0043] The applicant used the MgH obtained in Example 1 2 -FeNi@C composite materials were subjected to hydrolysis reaction at different temperatures (30℃, 40℃, 50℃, 60℃). Figure 7As shown, the reaction rate increases with the increase of temperature.
[0044] In order to calculate and analyze the MgH obtained in Example 1 2 The activation energy of the hydrolysis reaction of the -FeNi@C composite material was first fitted using the John-Mehl-Avrami (JMA) equation (Formula 1), and then the Arrhenius equation (Formula 2) was used to further calculate and analyze the activation energy of the hydrolysis reaction of Example 1. The formula is as follows: α = 1-exp(-kt n )(Formula 1), ln k=ln AE a / RT (Formula 2); where α represents the conversion rate of the hydrolysis reaction at a given time t; k represents the reaction constant related to temperature; A represents the pre-exponential factor, which is called the Arrhenius constant and has the same unit as k; n represents the Avrami constant, which represents the rate stage of nucleation and growth; E a represents activation energy, R represents gas constant, and T represents solution temperature.
[0045] like Figure 8 As shown, the MgH obtained in Example 1 was finally calculated after fitting by the JMA equation. 2 The activation energy of the hydrolysis reaction of the -FeNi@C composite material is 22.38461 kJ / mol, which is much smaller than the activation energy of pure magnesium hydride, indicating that the hydrolysis reaction activity of magnesium hydride in Example 1 is higher, the hydrolysis kinetics of magnesium hydride is greatly enhanced, the reaction stability is reduced, and the hydrogen production amount and hydrogen production rate are increased.
[0046] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a FeNi@C catalytically modified magnesium hydride hydrogen storage material, characterized in that: The following steps are involved: S1. Preparation of catalyst precursor: Glucose, ferric nitrate nonahydrate and nickel nitrate hexahydrate were dissolved in deionized water, and then urea was added and stirred at room temperature for 1 hour until all the reagents were dissolved. The obtained solution was transferred to a hydrothermal reactor for heating and heat treatment and kept warm for reaction. The solution was then taken out and centrifuged and washed 3 times. The obtained product was placed in an oven for drying to obtain a catalyst precursor, which was recorded as FeNi-LDH; S2. Preparation of catalyst: placing FeNi-LDH in a tube furnace and heating it for pyrolysis to obtain a catalyst, which is denoted as FeNi@C; S3. Preparation of FeNi@C catalytically modified magnesium hydride hydrogen storage material: MgH2 and FeNi@C were ball-milled using a planetary ball mill. After running for 10 minutes, it was stopped for 5 minutes and then reversely ball-milled. The total ball-milling operation time was 5 hours. After the ball-milling was completed, a MgH2-FeNi@C composite material was obtained.
2. The method for preparing the FeNi@C catalytically modified magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step S1, the ratio of glucose, ferric nitrate nonahydrate, nickel nitrate hexahydrate, deionized water and urea is 3 mmol:1.5 mmol:3 mmol:50 mL:8 mmol.
3. The method for preparing the FeNi@C catalytically modified magnesium hydride hydrogen storage material according to claim 2, characterized in that: In step S1, the conditions for heating and heat preservation in the hydrothermal reactor are: heat preservation at 180°C for 12 hours; and the conditions for oven drying are: drying at 40°C for 12 hours.
4. The method for preparing the FeNi@C catalytically modified magnesium hydride hydrogen storage material according to claim 3, characterized in that: In step S2, the conditions for the pyrolysis are: heating to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and then maintaining the temperature for 2 hours.
5. The method for preparing the FeNi@C catalytically modified magnesium hydride hydrogen storage material according to claim 4, characterized in that: In step S3, the mass ratio of MgH2 and FeNi@C is 90-99:10-1; the mass ratio of balls to materials during ball milling is 40:1, and the ball milling speed is 300 r / min.
6. The method for preparing the FeNi@C catalytically modified magnesium hydride hydrogen storage material according to claim 5, characterized in that: In step S3, the mass ratio of MgH2 to FeNi@C is 95:
5.
7. A FeNi@C catalytically modified magnesium hydride hydrogen storage material, characterized in that: The method is prepared according to any one of claims 1 to 6.
8. A method for producing hydrogen by hydrolysis, characterized in that: The FeNi@C catalytically modified magnesium hydride hydrogen storage material according to claim 7 or the FeNi@C catalytically modified magnesium hydride hydrogen storage material prepared by the preparation method according to any one of claims 1 to 6 is added to the magnesium chloride solution, and the hydrolysis reaction is completed under a constant temperature water bath and magnetic stirring, and the generated hydrogen is collected by the drainage method.
9. The method for producing hydrogen by hydrolysis according to claim 8, characterized in that: The concentration of the magnesium chloride solution is 0.1 mol / L, and the dosage ratio of the magnesium chloride solution to the FeNi@C catalytically modified magnesium hydride hydrogen storage material is 10 mmol:1 g.
10. The method for producing hydrogen by hydrolysis according to claim 9, characterized in that: The temperature of the water bath is 30°C, 40°C, 50°C or 60°C, the speed of the magnetic stirring is 200 r / min, and the hydrolysis reaction time is 1 h.